Exploring consumer intentions to use the M-pesa financial service: a comparative study of low-income communities in Kenya and South Africa - Osah, Olam (My University, 2013)
Abstract Recent times have witnessed increasing availability of mobile technology-based products/services in developing regions such as Africa. However, the extant literature has not traditionally focused on understanding the adoption and use of these technologies by consumers in these parts of the world. This gap cannot be ignored and the need to investigate consumer intention to use mobile based-technology in this region is becoming paramount to their successful implementation. One such mobile-based technology is the M-pesa financial service. The current study merged appropriate theories that could predict consumer intention to use this M-pesa service in two African countries, Kenya and South Africa. First, the two countries were compared in an attempt to provide an explanation of why the launch of the M-pesa service has been more successful in Kenya than in South Africa. It then examined the effects of the Technology Acceptance Model variables (perceived usefulness and perceived ease of use), subjective norm from the Theory of Reasoned Action, self efficacy from the Social Cognitive Theory, and six dimensions of Switching Costs, on consumers intention to use M-pesa. To measure the study’s variables, validated scales from the IS literature, social psychology literature, and economics literature were identified and adopted. Data were collected using paper based survey instruments from individuals residing in low-income communities in Kenya (N=265) and South Africa (N=150), thus a total of 415 responses. The results indicate there are correlations between all variables and intention to use, however, only perceived usefulness, perceived ease of use, and subjective norms have a direct influence on intention to use M-pesa. The model explained 33.1% of the variance in intention to use M-pesa. The results suggest that while switching costs do not have a direct influence on intention to use, some of their effects are mediated in predicting intention to use. Thus, this study has paved the way for future testing and enhancement of the study’s model. The study’s contribution to theory and practice are also presented.
Keywords: M-pesa; Mobile technology-based products/service; Intention to use; Consumer behaviour; Computing behaviour; TAM; TRA; SCT; Switching cost